Shell occupation as a limiting factor for Pagurus brevidactylus (Stimpson, 1859) in the Marine State Park of Laje de Santos, Brazil. Issue 1 (2nd January 2019) - da Silva, Alexandre Ribeiro; Galli, Giovanna Mielli; Stanski, Gilson; De Biasi, Juliana Beltramin; Davanso, Thiago Maia; Cobo, Valter José; Castilho, Antonio Leão
ABSTRACT: Hermit crabs are soft-abdomen decapods. They depend upon gastropod shells for protection, with the latter influencing growth rate, mortality and reproduction. The present work aims to provide information about the biology and reproduction of Pagurus brevidactylus in a conservation area in Brazilian southeastern littoral. The material was sampled through active searching by SCUBA diving and refuge traps. We analyzed population structure, fecundity, reproductive output (RO), reproductive periodicity and shell utilization for P. brevidactylus . In total, 54 males, 18 non-ovigerous females, 34 ovigerous females and 10 juveniles were sampled. The females had a fecundity of 69.5 ± 65 eggs, which was lower than that compared to other populations from different localities. The RO ranged from 1.48% to 63.04%, with a mean of 26.75 ± 18.23%. There was a positive relationship between egg number and female size. The animals had continuous reproduction, but they reached smaller maximum sizes when compared with other populations. The shell occupation pattern was also different from other localities, the shells of Phrontis alba being the most occupied; this shell has a smaller size when compared to others that P. brevidactylus occupies in other localities. Therefore, P. alba could have had limited the growth and reproduction of P. brevidactylus.